Tourism promotion and power creating images, creating identities - Morgan, Nigel (John Wiley & Sons, 1998)
Informed by modern marketing theory, this book offers a unique approach by taking a comprehensive, synthesised and integrated sociological and cultural approach to tourism marketing. It focuses on controversial issues of tourism imagery, highlighting issues such as gender, sexuality and race as key determinants of tourism power dimensions. Students of tourism will find this book a thought-provoking and conceptual evaluation of the subject. Practitioners will find value in the discussion of how the issues raised have been integrated throughout the case studies.